logo
or
search
upload

Fill in the blanks by suitable conversion of units : <br> (a) 1kg m^2 s^(-2) = g cm^2 s^(-2) (b) 1m = ……. Light year (c ) 3ms^(-2) = ….. Km h^(-2) <br> (d) G = 6.67 xx10^(-11) Nm^2 kg^(-2) = …… cm^3 s^(-2) g^(-1)

Apne doubts clear karein ab Whatsapp par bhi. Try it now.
CLICK HERE

Loading DoubtNut Solution for you

Watch 1000+ concepts & tricky questions explained!

65.2 K+ views | 3.3 K+ people like this

   
Share
Share

Answer Text

Solution :
`(a) 1kg =10^(3) g` <br> `1 kg m^2 s^(–2) = 1 kg × 1 m^2 × 1 s^(–2)` <br> `=10^3 g × 10^4 cm^2 × 1 s^(–2) = 10^7 g cm^2 s^(–2)` <br> (b) light year is the total distance travelled by light in one year <br> 1 y =speed of ligtht ×one year <br> `= (3 × 10^8 m/s) × (365 × 24 × 60 × 60 s)` <br> `= 9.46 × 10^(15) m` <br> `:.1m =1/(9.46xx10^(15)) 1.057xx10^(-16) ly` <br> (c) `1m=10^(–3) km` <br> Again `1s=1/3600 h` <br> `1 s^(–1) = 3600 h^(–1)` <br> `1 s^(–2) = (3600)^2 h^(–2)` <br> `∴3 m s^(–2) = (3 × 10'^(–3) km) × ((3600)^2 h^(–2)) = 3.88 × 10^4 km h^(–2)` <br> (d) `1N=1kg ms^(–2)` <br> `1 kg = 10^(–3) g^(–1)` <br> `1m^(3) =10^(6) cm^(3)` <br> `∴ 6.67 × 10^(–11) N m^2 kg^(–2) = 6.67 × 10^(–11) × (1 kg m s^(–2)) (1 m^2) (1 s^(–2))` <br> `= 6.67 × 10^(–11) × (1 kg × 1 m^3 × 1 s^(–2)) = 6.67 × 10^(–11) × (10^(–3) g^(–1)) × (10^6 cm^3) × (1 s^(–2)) = 6.67 × 10^(–8) cm^3 s^(–2) g^(–1)`

bottom open in app